A new real-time PCR assay to specifically detect crustaceans in vegan raw materials and vegan shrimps. Issue 4 (3rd April 2022) - Cottenet, Geoffrey; Blancpain, Carine
Abstract: Contamination of vegan products and vegan shrimps with real shrimps and crustaceans must be avoided to comply with vegan claims, even more for preventing strong allergenic reactions. Therefore, the detection of crustaceans must be reliable and sensitive enough for authenticity, traceability, and food safety purposes. A new real-time PCR assay was developed targeting the mitochondrial 16S rRNA gene of crustaceans and was optimised to avoid critical mismatches with primers and probe. By testing several crustacean species and common food ingredients, the method was demonstrated to be specific to crustaceans only. To comply with the limit of non-vegan contamination established at 0.1% (w/w) by the European Vegetarian Union, dedicated cut-off CT values were determined on vegan raw materials and on vegan shrimps spiked with crustacean materials. The method reached a sensitivity ≤ 0.0005% (w/w), which was further confirmed on reference materials containing a similar amount of crustacean.